PGC-mediated conservation strategies for germplasm resources of Rugao Yellow chicken and Shouguang chicken in China - Guangzheng Liu; Wenjie Ren; Kai Jin; Dan Zheng; Qisheng Zuo; Yani Zhang; Guohong Chen; Bichun Li; Yingjie Niu (Journal of Integrative Agriculture, 2025)
Germplasm resources are essential for the sustainable development of biodiversity and husbandry of local chickens, as well as for the breeding and industry of superior quality chickens. Unfortunately, many local and indigenous chicken breeds are at risk of declining numbers, emphasizing the need to conserve breed resources for endangered chickens. Primordial germ cells (PGCs) are crucial for preserving germplasm resources by inheriting genetic information from parents to offspring and ensuring stability of genetic material between germlines. In this study, PGCs were isolated from chicken embryos’ gonads and cultured in FAcs medium without feeder cells. Over a period of approximately 40 d, the cells proliferated to a number of up to 106, establishing various cell lines. Particularly, 18 PGC lines were created from Rugao Yellow chicken and Shouguang chicken, with an efficiency ranging from 39.1 to 45%. Furthermore, PGCs that had been cultured for 40 passages exhibited typical PGC characteristics, such as glycogen staining reaction, and expression of pluripotency and reproductive markers. These results confirm that PGCs maintain stem cell properties even after long-term in vitro culture. Additionally, PGCs cryopreserved for up to 120 d remained viable, maintained typical PGC morphologies, and possessed stable cell proliferation ability. Through intravascular injection into chicken embryos, green fluorescent protein (GFP)-PGCs were found in the recipient embryos’ gonads and could develop into gametes to produce offspring, indicating that even after extended culture, PGCs retain their migratory and lineage-transmitting capabilities. This research offers valuable insights into the in vitro cultivation and preservation of PGCs of Chinese indigenous chickens. The findings of this study can be applied in transgenic chicken production and the preservation of genetic resources of indigenous chicken breeds.